Genetic parameter estimates for plasma oxidative status traits in slaughter pigs - Ntawubizi, Martin (J Anim Sci, 2019)
The aim of the present study was to assess the effect of sex and to estimate genetic parameters for several traits related to plasma oxidative status in slaughter pigs, i.e., ferric reducing ability of plasma (FRAP), concentrations of α-tocopherol and malondialdehyde (MDA), and glutathione peroxidase (GPx) activity. Blood samples were collected at slaughter from 477 Piétrain × (Landrace × Large White intercross) pigs of 2 performance test stations. Heritabilities (±SE) of plasma oxidative status traits as well as their phenotypic and additive genetic correlations with animal performance traits were estimated with multiple-trait REML animal models using VCE software. Results displayed no significant difference between barrows and gilts for FRAP and α-tocopherol in plasma. However, gilts had a significantly higher concentration of MDA and lower GPx activity compared with barrows. Heritability estimates were high for GPx (0.55 ± 0.05), and medium to low for α-tocopherol (0.30 ± 0.06), FRAP (0.22 ± 0.05), and MDA (0.15 ± 0.04). Estimated additive genetic and phenotypic correlations between these four traits were generally low, except for a negative additive genetic correlation between FRAP and GPx of −0.45 (±0.23). Additive genetic correlations between plasma oxidative status traits and animal performance traits were also generally absent or low with maximum values of ~0.3. Parameter estimates in this study have to be interpreted with caution because of the small size of the dataset. Nevertheless, it may be concluded that there is considerable additive genetic variance for plasma oxidative status traits in slaughter pigs. More research is warranted on the genetic determination of oxidative stress in farm animals and its relevance in breeding programs.